GREEN SYNTHESIS, CHARACTERIZATION OF SILVER NANOPARTICLES OF A MARINE RED ALGA SPYRIDIA FUSIFORMIS AND THEIR ANTIBACTERIAL ACTIVITY - Murugesan, Subbiah; Bhuvaneswari, Sundaresan; Sivamurugan, Vajiravelu (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: In the present system, the green synthesis of silver nanoparticles using marine the red alga Spyridia fusiformis and antibacterial activity was carried out. Methods: The seaweed extract was used for the synthesis of AgNPs at room temperature. The silver nanoparticles were characterized by using UV–Visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscope and X-ray diffraction (XRD) techniques. The antibacterial activity of biosynthesized silver nanoparticles was carried out by disc diffusion method against pathogenic bacteria. Results: The UV-visible spectroscopy revealed surface plasmon resonance at 450 nm. The FT-IR measurements showed the possible functional groups responsible for the formation of nanoparticles. The X-ray diffraction analysis showed that the particles were crystalline in nature. TEM micrograph has shown the formation of silver nanoparticles with the size in the range of 5–50 nm. The silver nanoparticles synthesized from the S. fusiformis showed higher activity and proved their efficacy in controlling the pathogenic bacterial strains. The nanoparticles showed highest inhibition activity on K. pneumaniae and S. aureus up to 26 and 24±0.01 mm at 100 μg/ml of nanoparticles. Conclusion: The synthesised AgNPs have shown the best antibacterial activity against human pathogens E. coli, K. pneumoniae, S. aureus and P. aeruginosa. The above eco-friendly AgNPs synthesis procedure could be a viable solution for industrial applications in the future and therapeutic needs.